ANALISIS PENGARUH ORIENTASI PASAR DAN ORIENTASI TEKNOLOGI TERHADAP KINERJA PERUSAHAAN MELALUI INTEGRASI RANTAI PASOKAN SEBAGAI VARIABEL INTERVENING (Studi pada Industri Kecil dan Menengah Bordir di Kota Tasikmalaya) - Rizky Awalul Ramdani; Retno Hidayati (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study was conducted to examine the impact of market orientation and technology orientation on firm performance at Bordir Small Medium Industry (SMI) in Tasikmalaya City using supply chain integration as an intervening variable. The populations of this study were Bordir Small Medium Industry (SMI) entrepreneurs in Tasikmalaya City.. The number of samples used in this study was 150 respondents, and the data were gathered via a questionnaire. The analytical method used in this study was the Structural Equation Modeling (SEM) analysis technique with the AMOS 26.0 analysis tool. The results showed that all independent variables, namely market orientation, technology orientation and supply chain integration had a positive and significant effect on firm performance. Furthermore, supply chain integration has a major impact on business performance through moderating the relationship between market orientation and technological orientation at Bordir Small Medium Industry (SMI) in Tasikmalaya City